Analisis Kinerja Personel Pertolongan Kecelakaan Penerbangan Dan Pemadam Kebakaran Dalam Mewujudkan Keselamatan Penerbangan Di Bandar Udara Tunggul Wulung Cilacap - Diqy Surya Hidayatullah; Rezty Fauziah Novianty Z. (Jurnal Multidisiplin Indonesia, 2024)
Aviation safety is always the foremost priority and a serious concern that must be ensured for service users during the provision of air transportation services, as the risk of accidents resulting from an airplane crash is significantly higher compared to land and sea transportation modes. One of the units tasked with ensuring aviation safety at airports is the Aircraft Rescue and Fire Fighting. Every officers on duty must carry out their duties and functions to the fullest to ensure satisfactory performance. The suboptimal implementation of the main tasks of the ARFF unit at Tunggul Wulung Airport in maintenance and routine training will affect the existing performance. So the author conducted this research to determine how the officers of the ARFF unit handle incidents and the efforts made by officers to enhance operational proficiency in this unit. This research employs a qualitative approach with a semi-structured interview method conducted on the officers of the ARFF unit, direct observation at the ARFF unit office, and documentation of ARFF officers activities. The stages in analyzing data in this study involve data reduction, data presentation, and drawing conclusions. The results this research explain that the performance of the ARFF unit at Tunggul Wulung Airport is already good when measured by several existing indicators. However, there is a need to maximize the implementation of core tasks in maintenance and routine training so that officers performance during emergency operational activities can be more optimal.